Copper-catalyzed synthesis of 2-unsubstituted, n-substituted benzimidazoles - Hirano, Keiichi; Biju, Akkattu T.; Glorius, Frank (Journal of Organic Chemistry, 2009)
An efficient copper-catalyzed intramolecular arylation of formamidines forming 2-unsubstituted benzimidazoles in excellent yields is reported. Sixteen examples bearing sterically demanding substituents on nitrogen like Mes, 2,6-diisopropylphenyl, or 2-tert-butylphenyl and tolerating various functional groups demonstrate the utility of this method.